2016
DOI: 10.2147/ott.s111431
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological role of miR-30a-5p in hepatocellular carcinoma tissues and prediction of its function with bioinformatics analysis

Abstract: BackgroundIt has been reported that deregulation or dysfunction of microRNAs (miRNAs) plays an essential part in the hepatocarcinogenesis. However, the contribution and mechanism of microRNA-30a-5p (miR-30a-5p) in hepatocellular carcinoma (HCC) remains largely unknown. Therefore, our aim was to investigate the clinicopathological role of miR-30a-5p in HCC tissues and explore its potential pathways in this study.MethodsThe expression of miR-30a-5p was measured in 95 HCC and adjacent noncancer tissues by real-ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…From previous reports, miR-30a-5p is known to play an anti-oncogenic role in tumourigenesis. For instance, low expression of miR-30a-5p correlates with tumour metastasis, a high tumour stage, as well as tumour-capsule infiltration [20]. Additionally, induction of miR-30a-5p enhances drug sensitivity by inhibiting Beclin-1 in human small cell lung cancer [21].…”
Section: Discussionmentioning
confidence: 99%
“…From previous reports, miR-30a-5p is known to play an anti-oncogenic role in tumourigenesis. For instance, low expression of miR-30a-5p correlates with tumour metastasis, a high tumour stage, as well as tumour-capsule infiltration [20]. Additionally, induction of miR-30a-5p enhances drug sensitivity by inhibiting Beclin-1 in human small cell lung cancer [21].…”
Section: Discussionmentioning
confidence: 99%
“…Reduced expression of miR-142 was found in some types of cancers such as osteosarcoma and renal cancer [ 11 , 12 ], but this has not observed in HCC. Previous studies have demonstrated that miRNAs were involved in the regulation of HCC invasion and migration, for example, miR-30, miR-135, and miR-1299 [ 28 30 ]. In this study we identified that miR-124 suppresses HCC invasion and migration through down-regulation of THBS4 , and loss of miR-124 leads to over-expression of THBS4 thereby promoting HCC invasion and migration.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-30a-5p plays vital roles in the carcinogenesis and progression of various malignancies via different molecular mechanisms [ 123 ]. miR-30a-5p expression is significantly lower in HCC tumor tissue compared with adjacent normal tissue and is correlated with tumor nodes, metastasis, the tumor–node–metastasis stage, portal vein tumor embolus, vascular invasion, and tumor capsule status [ 124 ]. The aberrant glucose metabolism in cancer cells, reflecting a shift away from oxidative phosphorylation towards aerobic glycolysis during tumorigenesis (i.e., Warburg effect), is associated with resistance to chemotherapeutic agents.…”
Section: Genes Associated With Sorafenib Resistancementioning
confidence: 99%